Wave-absorbing material based on reduction, carbonization and modification of fly ash magnetic separation product and preparation method of wave-absorbing material
By reducing and carbonizing the fly ash magnetic separation products, an absorbing material containing Fe, Fe3C and C was prepared, which solved the problems of large thickness, high density and insufficient absorption capacity of Fe3O4 materials, and achieved efficient absorption of electromagnetic waves for specific frequency under low matching thickness.
Patent Information
- Application Number
- CN202510016060.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
As an electromagnetic wave absorbing material, Fe3O4 has problems such as large matching thickness, high density and insufficient reflection loss absorption capacity, and it is difficult to meet the requirements of low matching thickness, light weight, wide effective absorption bandwidth and high reflection loss absorption capacity.
By reducing and carbonizing the fly ash magnetic separation product and carbonizing it with ethylene, it is prepared by reducing carbonizing modification of fly ash magnetic separation product. This process includes hydrogen reduction under argon protection, followed by carbonization in a pure ethylene atmosphere, controlling the carbonization temperature between 600°C and 800°C, the carbonization time between 5-15 minutes, and the ethylene gas flow rate between 5-20 sccm.
Samples containing Fe, Fe3C and C were successfully prepared. By controlling the carbonization time and ethylene gas flow rate, the sample has the ability to absorb electromagnetic waves in a specific frequency under low matching thickness, and improves the absorption performance and reflection loss absorption capacity.
Smart Images

Figure CN119815813A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of wave-absorbing materials, and in particular relates to a wave-absorbing material based on reduction and carbonization modification of fly ash magnetic separation products and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of microwave communications, computers and other portable electronic devices, electromagnetic radiation pollution and electromagnetic wave interference have continued to affect residents' lives. In order to solve this problem, researchers are working hard to develop a high-efficiency microwave absorbing material that has both high microwave absorption efficiency and low thickness.
[0003] As a kind of magnetic material, Fe3O4 has the characteristics of high magnetic permeability, high magnetic loss, high saturation magnetization and good stability, and has a good future in electromagnetic wave absorption. In terms of wave absorption performance, the electromagnetic wave loss of Fe3O4 includes conductivity loss, ion polarization loss in dielectric loss, natural resonance loss, domain wall resonance loss and exchange resonance loss in magnetic loss. The characteristics of multiple loss mechanisms have also attracted the interest of many researchers in Fe3O4 as an electromagnetic wave absorption material. However, Fe3O4 also has its common disadvantages as a ferrite, namely, large matching thickness and high density, Snoek limit and poor impedance matching, so it is difficult to simultaneously meet the requirements of low matching thickness, light weight, wide effective absorption bandwidth and high reflection loss absorption capacity.
[0004] Therefore, in order to improve the electromagnetic absorbing ability of Fe3O4 and meet the current demand for absorbing materials, it is necessary to adjust the parameters of Fe3O4 itself and modify the fly ash reduction product to obtain a new type of absorbing material. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a wave absorbing material based on reduction and carbonization modification of fly ash magnetic separation products and a preparation method thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A method for preparing a wave absorbing material based on reduction carbonization modification of fly ash magnetic separation products comprises the following steps:
[0009] Using ethylene to carbonize and modify the fly ash reduction product to obtain the microwave absorbing material based on the fly ash magnetic separation product reduction and carbonization modification;
[0010] The carbonization temperature in the carbonization modification process is 600° C.-800° C.; the carbonization time is 5-15 min; and the gas flow rate of ethylene is 5-20 sccm.
[0011] Optionally, the carbonization temperature in the carbonization modification process is 600° C., 700° C. or 800° C.; the carbonization time is 5 min, 10 min or 15 min; and the gas flow rate of ethylene is 5 sccm, 10 sccm, 15 sccm or 20 sccm.
[0012] Furthermore, the carbonization temperature in the carbonization modification process is 800° C.; the carbonization time is 5 min; and the gas flow rate of ethylene is 5 sccm.
[0013] Optionally, the preparation method of the fly ash reduction product is:
[0014] The fly ash is subjected to magnetic separation and hydrogen reduction in sequence to obtain the fly ash reduction product.
[0015] Furthermore, the magnetic separation adopts a pull-out dry magnetic separation, and the magnetic separation product is obtained after 31 separation rings are magnetically separated;
[0016] The reduction temperature in the hydrogen reduction process is 800° C. and the reduction time is 1 hour.
[0017] The second technical solution of the present invention:
[0018] A wave absorbing material based on reduction and carbonization modification of fly ash magnetic separation products is prepared by the above preparation method.
[0019] Optionally, the wave absorbing material based on reduction and carbonization modification of fly ash magnetic separation products is a core-shell structure formed by Fe and Fe3C.
[0020] Optionally, the strongest reflection loss value of the wave absorbing material based on the reduction and carbonization modification of fly ash magnetic separation products is -39.19 dB at 11.68 GHz, and the matching thickness is 2.5 mm.
[0021] Compared with the prior art, the present invention has the following advantages and technical effects:
[0022] The present invention carbonizes the 800°C, 2h reduction sample under the conditions of 600°C to 800°C carbonization temperature, 5 to 15min carbonization time, and 5 to 20sccm ethylene gas flow rate. XRD results show that the sample containing Fe3C is successfully prepared, and SEM results show that the shell layer on the surface of the sample particles carbonized at 800°C, 5min, and 20sccm is evenly distributed. VSM test results show that carbonization time is a key factor in controlling the magnetic properties of the sample. Too long carbonization time will cause a large amount of carbon to be deposited in the sample, causing the magnetic properties of the sample to decrease. Electromagnetic parameter and RL spectrum results show that increasing the carbonization temperature is conducive to reducing the optimal RL value matching thickness of the sample; while too long carbonization time will increase the C content in the carbonized sample, affect the complex dielectric constant and complex magnetic permeability of the sample, and reduce the wave absorption performance of the sample. In addition, the present invention can achieve the absorption ability of the sample to electromagnetic waves of a specific frequency under the condition of a low matching thickness of 2.5mm by controlling the ethylene gas flow rate to control the ratio between Fe and Fe3C. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0024] Figure 1 This is a physical picture of the magnetic rod housing with a separation ring in the pull-out dry magnetic separation device of the present invention;
[0025] Figure 2 It is a schematic diagram of the working principle of the pull-type dry magnetic separation device of the present invention;
[0026] Figure 3 The XRD spectrum of the carbonized sample in the range of 500°C to 800°C of the present invention;
[0027] Figure 4 The XRD patterns of the samples of (a) 5 to 15 min carbonization time and (b) 5 to 20 sccm ethylene flow rate of the present invention are as follows;
[0028] Figure 5 The SEM images of (a) the reduction product, (b) the carbonized sample at 600°C for 5 min, (c) the carbonized sample at 600°C for 15 min, and (d) the carbonized sample at 800°C for 5 min of the present invention;
[0029] Figure 6 The XPS spectra of (a) Fe 2p and (b) C 1s of the sample carbonized at 800°C for 5 min of the present invention;
[0030] Figure 7 It is the hysteresis loop of samples with different carbonization temperatures in the range of 600°C to 800°C of the present invention;
[0031] Figure 8 The hysteresis loops of samples with different carbonization times within the range of 5 to 15 minutes of the present invention;
[0032] Fig. 9 (a) dielectric real part, (b) dielectric imaginary part, (c) magnetic permeability real part, (d) magnetic permeability imaginary part of the samples of the present invention at different carbonization conditions in the range of 600°C to 800°C and 5 to 15 minutes at 2 to 18 GHz;
[0033] Fig.10 The dielectric loss tangent and magnetic loss tangent diagrams of the reduction product of the present invention at different carbonization temperatures and carbonization times;
[0034] Fig.11 The three-dimensional surface diagram of the reflection loss value of the sample of the present invention (a) magnetic separation product; (b) 600℃, 5min; (c) 700℃, 5min; (d) 800℃, 5min; (e) 600℃, 10min; (f) 600℃, 15min at different thicknesses and changes with frequency;
[0035] Fig.12 The quarter-wavelength theoretical matching thickness, reflection loss and normalized impedance matching curve of (a) the carbonized sample at 600°C for 5 min; (b) the carbonized sample at 800°C for 5 min of the present invention;
[0036] Fig.13 It is the hysteresis loop of the sample of controlling the change of ethylene flow rate within the range of 5 to 20 sccm of the present invention;
[0037] Fig.14 (a) dielectric real part, (b) dielectric imaginary part, (c) magnetic permeability real part, (d) magnetic permeability imaginary part at 2 to 18 GHz for samples prepared by changing the ethylene gas flow rate within the range of 5 to 20 sccm of the present invention;
[0038] Fig.15 (a) dielectric loss tangent and (b) magnetic loss tangent of the reduction product of the present invention at different ethylene flow rates;
[0039] Fig.16 The three-dimensional surface diagram of the reflection loss value of the samples with ethylene gas flow rates of (a) 5 sccm, (b) 10 sccm, (c) 15 sccm, and (d) 20 sccm at different thicknesses as a function of frequency;
[0040] Fig.17 It is the quarter-wavelength theoretical matching thickness, reflection loss and normalized impedance matching curve of the sample of the present invention at 800° C., 5 min and 5 sccm ethylene flow rate. DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0042] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0043] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0044] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0045] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0046] The chemical composition and corresponding content (measured by XRF) of the fly ash used in the present invention are shown in Table 1 below.
[0047] Table 1 Chemical composition and corresponding content of fly ash
[0048]
[0049] Example 1
[0050] A method for preparing a microwave absorbing material based on fly ash reduction products comprises the following steps:
[0051] (1) Magnetic separation of fly ash: Dry magnetic separation is used to separate fly ash. The specific operation is: the fly ash is slowly poured into the self-made dry magnetic separation equipment at a uniform speed for magnetic separation, and the product is collected at the discharge port, which is called the magnetic product. The gray-white powder obtained at the tailings port is the tailings.
[0052] The self-made dry magnetic separation equipment (reference patent CN 116328937 A) consists of a magnetic rod and a non-magnetic shell, on which 31 separation rings with a height of 3 mm and a width of 7 mm are arranged. Figure 1 As shown. The separation ring is in a circular shape, and its function is to promote the relative movement of the magnetic and non-magnetic components in the entrained clusters to achieve effective separation. When the device is used for experiment, a quantitative sample is poured onto the separation ring of the device, and the sample is magnetically separated by 31 separation rings to obtain a magnetic separation product. The product mass, the iron oxide content in the product, and the iron recovery rate are calculated. The specific working principle of magnetic separation is: at the beginning of magnetic separation, Figure 2 As shown in position A in the figure, fly ash enters the magnetic separation device from the feed port, and the magnetic particles are attracted by the magnetic rod and adsorbed on the surface of the magnetic rod. At the same time, after the magnetic particles are magnetized by the magnetic rod, they can be regarded as small magnets, which interact magnetically with each other to form dense clusters. When clusters are formed, non-magnetic particles are entrained by adjacent magnetic particles, are also mixed in the clusters, and are adsorbed on the surface of the magnetic rod. As the clusters move to the right with the magnetic rod, the magnetic particles continuously jump over the separation ring, and the non-magnetic particles in the clusters continuously fall off. When the magnetic rod is pulled to position C, the non-magnetic particles basically disappear, and the magnetic particles are blocked by the baffle on the port, and fall to the discharge port under the action of their own gravity, and finally complete the dry magnetic separation; the results of magnetic separation (two parallel tests) are shown in Table 2:
[0053] Table 2
[0054]
[0055]
[0056] (2) Reduction of magnetic separation products: The magnetic separation products were placed in a TF55030A tubular furnace, heated to the target temperature under argon protection, and then kept reduced in a pure hydrogen atmosphere at a flow rate of 20 sccm; then, the furnace was cooled to room temperature under argon protection;
[0057] (3) Carbonization of the reduction product: The product after hydrogen reduction was placed in a TF55030A tubular furnace. The furnace temperature was raised to the target temperatures of 500°C, 600°C, 700°C, and 800°C under an argon protective atmosphere. Then, the carbonization experiment was carried out under a pure ethylene atmosphere at a flow rate of 5 sccm, 10 sccm, 15 sccm, and 20 sccm. The carbonization time was controlled to be 5 min, 10 min, and 15 min. The product was then cooled to room temperature under an argon atmosphere to obtain a product whose main component was Fe3C.
[0058] Effect verification
[0059] 1. Effect of carbonization conditions on the morphology of carbonized samples
[0060] The magnetic separation product sample was first reduced at 800°C for 1 h under hydrogen conditions, and then carbonized in the range of 500°C to 800°C. The carbonization time was selected as 5 minutes, and the ethylene flow rate during carbonization was 20 sccm. Figure 3 The XRD patterns of samples at different carbonization temperatures are shown in Figure 2. The results show that Fe3C is generated in all carbonized samples. When the carbonization temperature is increased to 600°C or above, several characteristic peaks of orthorhombic Fe3C are observed at 37.6°, 39.8°, 40.6°, 42.8°, 44.9°, 45.8°, 48.6°, 49.1°, 51.8°, and 57.9°. The corresponding standard PDF card is #35-0772, and the crystal planes corresponding to the characteristic peak positions are (121), (002), (2 01), (211), (102), (031), (112), (131), (221), (122) and (031); the characteristic peak of Fe3C in the sample after 700℃ is relatively obvious, indicating that the crystallization of Fe3C formed in the sample is good; the characteristic peak of Fe in the carbonized sample at 800℃ increases, and the characteristic peak of Fe3O4 in the sample disappears, which may be due to the reduction reaction of Fe3O4 in the sample with carbon element at high temperature to become Fe. The characteristic peak positions of SiO2 and C in the sample are close, but the content of SiO2 is relatively small. After high-temperature carbonization, a large amount of Fe3C is formed, and a large amount of C will be deposited on the surface of the sample. Therefore, the characteristic peaks appearing at the same position should be considered as C.
[0061] In order to further explore the effect of changing other carbonization conditions on the formation of Fe3C in the sample, it has been found in the temperature exploration that the sample can generate Fe3C with complete crystal surface composition at 600℃. Therefore, at the carbonization temperature of 600℃, the carbonization time is adjusted in the range of 5 to 15min. The XRD spectrum is as follows: Figure 4As shown in (a). The results show that after increasing the carbonization time, no new Fe3C phase crystal plane is generated, and the peak intensity of the C diffraction peak generated at 26.2° increases, and the corresponding crystal plane is (111); as the carbonization time increases, the peak value of the Fe3C diffraction peak increases, and the characteristic peak becomes more obvious, but compared Figure 3 The 700℃ and 800℃ samples still have some low degree of crystallization, indicating that the carbonization time has little effect on the formation of Fe3C, and the carbonization temperature plays a decisive role in the formation of Fe3C.
[0062] According to the influence of carbonization temperature and carbonization time on the formation of Fe3C, the combined effect of low carbon source and low carbonization temperature on the carbonization of the sample was prevented, and excessive deposition of C element on the surface of the material was avoided. In order to further explore the role of ethylene gas flow rate in the carbonization process, a carbonization temperature of 800°C and a carbonization time of 5 min were selected, and the ethylene flow rate was adjusted in the range of 5 to 20 sccm to carry out carbonization experiments on the reduced samples. Figure 4 (b) is the XRD spectrum of the sample with ethylene flow rate in the range of 5 to 20 sccm. It can be seen from the figure that all prepared samples can generate Fe3C phase with complete crystal plane; the Fe3C peak of the 5 sccm sample is relatively low, but the characteristic peak is obvious, indicating that the Fe3C phase has a good degree of crystallization; increasing the ethylene flow rate, it is found that the relative intensity of the characteristic peak of the Fe phase in the 20 sccm sample decreases, and the intensity of the characteristic peak of Fe3C increases significantly, indicating that increasing the ethylene flow rate can accelerate the reaction process of Fe and ethylene, and promote the generation of Fe3C phase to a certain extent.
[0063] Figure 5 The SEM images of the reduced sample (reduction temperature and time are 800℃ and 1h respectively) and the carbonized sample under different conditions. The SEM image of the sample prepared under 600℃, 5min and 20sccm is shown in (b) in 5. The surface morphology of the particles after carbonization changes significantly; but under this condition, clusters appear on only some of the particle surfaces, which are composed of filamentous carbon fibers; the clusters on the particle surface are unevenly distributed, and the clusters fail to completely wrap the Fe particles. The particle surface morphology is rough and has cracks. When the carbonization time is increased to 15min, the SEM image of the sample is shown in (c) in 5. There are a large number of clusters and gaps on the surface of the sample particles. These clusters are composed of flakes and fine granular substances, and the degree of cluster wrapping is complete, indicating that extending the carbonization time will change the deposition morphology of carbon on Fe particles. Under the conditions of 5min carbonization time and 20sccm ethylene flow rate, the morphology of the sample when the carbonization temperature is increased to 800℃ is shown in (d) in 5. Most of the particles in the sample are wrapped, and the wrapping is complete without obvious cracks. This wrapping is a carbon fiber shell. After wrapping, the particles are approximately spherical as a whole, and the shell has a fine pore structure. Combined with the crystal phase results of the XRD sample, it shows that the shell contains a large amount of Fe3C and C.
[0064] Figure 6 XPS spectra of Fe 2p and C1s of the carbonized sample at 800°C, 5 min, and ethylene flow rate of 20 sccm. Figure 6 The test results in (a) show that the peaks of Fe 2p are observed at ~711.8eV and ~724.6eV. The peak at ~711.8eV is split to indicate the presence of Fe, Fe 2+ 2p 3 / 2 , Fe 3+ 2p 3 / 2 and Fe 2P satellite peaks, with corresponding areas of 1539.2, 1472.8, 667.8, and 616.7. Based on the area of the Fe elemental peak, it is shown that a large part of the iron element in the carbonized sample exists as a single substance; and the peak at ~724.6 eV is indicated to be caused by Fe 3+ 2p 2 / 1 (726.89 eV) and Fe 2+ 2p 2 / 1 (725.11eV), the corresponding areas are: 1119.4, 1043.2. Figure 6 From (b), we can see that the carbon single bond peak at 284.83 eV is extremely high, with an area of 46819. Therefore, most of the carbon bonds in the sample exist in the form of single bonds. Figure 3 The XRD spectrum shows that more carbon in the sample exists in the form of Fe3C; in addition, a peak of double bond carbon is observed at 288.48eV.
[0065] 2. Effect of carbonization temperature and carbonization time on sample performance
[0066] In order to explore the effects of carbonization temperature, carbonization time and carbon source flow rate on the magnetic properties of samples, the present invention tests the carbonized samples prepared under different conditions by using a vibrating sample magnetometer. Figure 7 It is the hysteresis loop of samples with different carbonization temperatures in the range of 600℃ to 800℃ (carbonization time is 5min, ethylene flow rate is 20sccm) at room temperature. S 、M r and H C As shown in Table 3. Figure 7 From Table 3, we can see that the saturation magnetization M of the samples at 600℃, 700℃ and 800℃ is S The carbonization temperatures are 49.32emu / g, 46.52emu / g and 55.36emu / g respectively. S The change did not show a certain regularity. The M S The decrease in the value is caused by the increase in the Fe3C content in the sample; when the temperature is raised to 800℃, the Fe3O4 in the sample is further reduced and converted into Fe under the influence of carbon. Fe has a very high MS , resulting in the M of the 800℃ sample S It is obviously better than the samples at other carbonization temperatures; the M r and H C Compared with the magnetic separation sample (magnetic separation product) and the reduced sample, the carbonization temperature is increased, which will make the M r The value decreases.
[0067] Table 3 Magnetic properties of samples at different carbonization temperatures
[0068]
[0069] Figure 8 The hysteresis loops of samples with different carbonization times in the range of 5 to 15 min (carbonization temperature is 600 °C, ethylene flow rate is 20 sccm) are shown in Figure 2. S 、M r and H C As shown in Table 4. The results in the figure show that long-term carbon deposition will cause the M S The M of the sample decreased significantly with the increase of carbonization time. S Gradually decrease; M of the sample with carbonization time of 15min r Compared with the M of the 5min sample r Compared with the carbonized samples, the value of H is greatly reduced to 3.26emu / g, which means that the increase of C content in the carbonized samples will lead to a significant decrease in the magnetic properties of the materials; C There is little difference between them, which are 210.12Oe and 183.36Oe respectively.
[0070] Table 4 Magnetic properties of samples with different carbonization times
[0071]
[0072] Fig. 9The ε', ε", μ' and μ" spectra of the samples were prepared by changing the carbonization conditions within the range of ethylene flow rate of 20 sccm, 600℃~800℃ and 5~15min. Analysis of the spectra shows that the ε' values of all carbonized samples are significantly improved, with peaks appearing at frequencies of 4~5GHz. Large ε' will lead to poor impedance matching characteristics of the samples, and the ε' value of the 600℃, 15min sample is much larger than the ε' value of other samples, indicating that the ε' value increases with the increase of the C content in the sample. In the 2-5 GHz frequency band, the ε" value of the carbonized sample is negative, indicating that the dielectric properties of the sample have poor attenuation ability for electromagnetic waves in this frequency band. In the 6-18 GHz frequency band, the ε" value of the carbonized sample is significantly higher than the ε" value of the magnetic separation product; and double dielectric relaxation peaks appear in the 10 GHz and 12 GHz frequency bands. The dielectric relaxation peak is significantly weakened when the carbonization time is reduced. In addition, with the increase of carbonization temperature, the peak value of the dielectric relaxation peak increases first and then decreases. For the μ' of the sample, in the 2-4 GHz frequency band, except for 600℃, Except for the 15min sample, which showed a positive value, the rest were negative values. In the range of 4 to 18 GHz, the μ' values of all samples were much larger than the μ' of the magnetic separation products, indicating that the magnetic properties of the samples had a strong absorption capacity for electromagnetic waves in this band. In the initial stage, the μ" values of all carbonized samples were large, among which the initial value of the sample carbonized at 600℃ and 5min was the largest, and μ" rapidly decayed to the same level as the magnetic separation products in the range of 2 to 5 GHz. Near the 11 GHz frequency band, all carbonized samples showed a weak natural resonance peak.
[0073] Fig.10 It is the magnetic loss tangent and dielectric loss tangent of the sample of the reduction product at different carbonization temperatures and carbonization times. The figure shows that carbonization significantly improves the dielectric loss performance of the sample to electromagnetic waves, which is proportional to the carbonization time and inversely proportional to the carbonization temperature. μ It has drastic extreme value changes and some of them are negative, which will cause the sample to have no loss capacity for electromagnetic waves in the low frequency band.
[0074] In order to judge the absorption performance of carbonized samples for electromagnetic waves, the reflection loss value of the samples was observed. The complex dielectric constant and complex magnetic permeability of the samples prepared under carbonization conditions ranging from 600℃ to 800℃ and carbonization time ranging from 5 to 15 min were substituted into formulas (1) and (2) to calculate the RL values of samples with a thickness of 1 to 5.5 mm in the range of 2 to 18 GHz.
[0075]
[0076] Where: RL represents the reflection loss of the sample; Z in It represents the input impedance when the medium is the sample; Z0 represents the impedance when the medium is air. in It can be obtained from formula 4-2:
[0077]
[0078] Where: Z in represents the input impedance when the medium is a sample; f represents the propagation frequency of the electromagnetic wave; d represents the thickness of the sample; c represents the speed of light; μ r Represents the complex magnetic permeability of the sample; ε r represents the complex dielectric constant of the sample.
[0079] Fig.11 The three-dimensional surface diagram of the RL value of samples with different thicknesses at carbonization temperatures ranging from 600℃ to 800℃ and carbonization times ranging from 5 to 15min shows the change with frequency. The ethylene gas flow rate is 20sccm. It can be found from the figure that according to the effective absorption conditions of the material for electromagnetic waves (RL<-10dB), the reflection loss value and effective absorption bandwidth of all samples in this group are significantly improved. Among them, the 600℃, 5min sample has the best reflection loss value of -29.85dB at a sample thickness of 3.5mm, and the effective absorption bandwidth is 6.06GHz to 8.16GHz. When the carbonization time is extended to 15min, the sample reaches the best RL value at 5.84GHz, which is -20.68dB. The matching thickness is reduced to 2mm, and the effective absorption bandwidth is 5.61 to 6.24GHz. The overall wave absorption performance deteriorates. This is because as the carbonization time increases, the C content in the sample increases significantly, which makes the magnetic properties of the sample worse, reducing the ability of the magnetic loss mechanism to absorb and attenuate electromagnetic waves. In addition, increasing the carbonization temperature can reduce the matching thickness corresponding to the optimal reflection loss value of the sample. The optimal reflection loss value of the sample under the carbonization condition of 800℃ and 5min is -26.65dB, the effective absorption bandwidth is 6.5~8.9GHz, and the corresponding matching thickness is 2mm. Figure 5 The SEM image of the sample shows that the core-shell structure formed by Fe and Fe3C enables the sample to have good microwave absorption performance at a low thickness.
[0080] Fig.12 These are the quarter-wavelength theoretical matching thickness, reflection loss and normalized impedance matching curves of the 600℃, 5min sample and the 800℃, 5min sample. Fig.12 The impedance matching values of the two groups of samples (a) and (b) at the optimal reflection loss values are close to 1; their quarter-wavelength theoretical matching thicknesses are 3.5 mm and 2 mm, respectively, and the matching levels are n=6 and n=5, respectively.
[0081] 3. Effect of ethylene flow rate on sample performance
[0082] Fig.13The hysteresis loop of the sample with ethylene flow rate controlled in the range of 5-20 sccm (carbonization temperature of 800℃, carbonization time of 5min), its MS, Mr and HC are shown in Table 5. The results in the figure show that the MS of this group of carbonized samples is slightly different, all around 60emu / g, and significantly higher than the M of the magnetic separation product sample. S ; H between the samples in this group C and M r The values are also similar, among which H C The value is between 150Oe and 180Oe, while M r The M value of the reduced product sample r The values are similar, both about 4emu / g. Therefore, under the same carbonization temperature and carbonization time conditions, changing the content of carbon source has little effect on the magnetic properties of the sample. This can be attributed to the fact that at a carbonization temperature of 800℃, most of the Fe particle surfaces are wrapped by Fe3C shells, and the generated particles with core-shell layers react completely. At the same time, increasing the carbon source content will not cause excessive carbon deposition in the sample, so that the magnetic properties of the sample do not change significantly.
[0083] Table 5 Magnetic performance parameters of samples with different ethylene flow rates
[0084]
[0085] The ε' of the sample prepared at an ethylene flow rate of 20 sccm is too large. A large ε' will weaken the sample's ability to absorb electromagnetic waves. In order to further explore the impact of changing the ethylene flow rate on the electromagnetic parameters of the carbonized sample, the flow rate of ethylene gas is appropriately reduced and adjusted within the range of 5 to 20 sccm in the hope of obtaining a sample with better electromagnetic properties. Fig.14 The electromagnetic parameter spectrum of the carbonized samples with carbonization temperature of 800℃, carbonization time of 5min and different ethylene flow rates in the range of 5-20sccm. The results show that compared with the magnetic separation products, the real part of the complex dielectric constant ε' of the samples with ethylene gas flow rate of 5-20sccm increases significantly, and a peak appears at 4-6GHz, and the value of ε' decreases with increasing frequency. Double dielectric relaxation peaks are observed at 13GHz and 16GHz, and the dielectric relaxation peaks become more obvious with increasing ethylene gas flow rate. Similar to the samples carbonized under other conditions, the complex magnetic permeability μ' of the samples with ethylene gas flow rate of 5-20sccm also presents a negative value in the range of 2-4GHz, and a peak appears at 6GHz. The peak value decreases with increasing ethylene gas flow rate. The initial value of μ" of this group of samples is high, and it decays sharply in the range of 2-6GHz, and finally maintains the same level as the magnetic separation product samples.
[0086] Fig.15The magnetic loss tangent and dielectric loss tangent of the carbonized samples obtained by carbonizing the reduction product at different ethylene flow rates. The results show that the dielectric loss capacity of the sample is poor in the 2-4 GHz frequency band, and the dielectric loss performance in the 8-18 GHz frequency band is significantly better than that of the magnetic separation product; with the increase of ethylene flow rate, the low-frequency tanδ ε increases, while tanδ at high frequencies ε The magnetic loss tangent of the samples shows a significant difference, indicating that the magnetic loss capacity of the samples changes significantly within 2 to 4 GHz.
[0087] The three-dimensional surface diagram of the reflection loss value of the sample at different thicknesses changing with frequency by changing the ethylene gas flow rate in the range of 5 to 20 sccm is shown in Figure 2. Fig.16 As shown. The results show that when the ethylene flow rate is 5sccm, the prepared sample reaches the best RL value at 11.68GHz, which is -39.19dB, and the corresponding matching thickness is 5mm. When the ethylene flow rate increases, the Fe3C content generated in the sample increases, and the matching thickness corresponding to the best RL value of the sample decreases to 2.5mm, indicating that the increase of Fe content in the sample is conducive to obtaining better wave absorption performance at high thickness, while the increase of Fe3C content is conducive to making the sample obtain better wave absorption and energy absorption at low thickness. With the increase of ethylene gas flow rate, the best RL value of the sample gradually weakens. The best RL values of 5sccm, 10sccm, 15sccm, and 20sccm samples are -39.19dB (11.68GHz), -37.21dB (16.69GHz), -32.77dB (12.56GHz), and -26.65dB (7.44GHz), respectively, and the best RL value of the sample moves to low frequency. Therefore, adjusting the content of Fe and Fe3C in the sample can make the sample have good absorption ability in a specific band.
[0088] Fig.17 The quarter-wavelength theoretical matching thickness, reflection loss and normalized impedance matching curves of the sample at 800°C, 5 min and 5 sccm ethylene flow rate are shown. The optimal reflection loss value of the carbonized sample moves toward high frequency, corresponding to a normalized impedance matching value of 0.87, and the optimal matching thickness level is n = 9. Therefore, the carbonized samples all conform to the quarter-wavelength matching model and impedance matching theory.
[0089] In summary, the present invention successfully prepared samples containing Fe, Fe3C and C by carbonizing the 800℃, 2h reduction sample under the conditions of 600℃~800℃ carbonization temperature, 5~15min carbonization time, and 5~20sccm ethylene gas flow rate. Carbonization time is a key factor in controlling the magnetic properties of the sample. A carbonization time of 15min will cause a significant decrease in the magnetic properties of the sample. Increasing the carbonization temperature is conducive to reducing the optimal RL value matching thickness of the sample; while too long a carbonization time will increase the C content in the carbonized sample, affect the complex dielectric constant and complex magnetic permeability of the sample, and reduce the wave absorption performance of the sample. At a carbonization temperature of 800℃, a carbonization time of 5min, and an ethylene gas flow rate of 5sccm, the carbonized sample has an optimal RL value of -39.19dB at 11.68GHz. Controlling the ethylene gas flow rate to achieve the control of the ratio between Fe and Fe3C can achieve the sample's ability to absorb electromagnetic waves of a specific frequency at a low matching thickness of 2.5mm.
[0090] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing an absorbing material based on reduction carbonization modification of fly ash magnetic separation products, characterized in that: The following steps are involved: Using ethylene to carbonize and modify the fly ash reduction product to obtain the microwave absorbing material based on the fly ash magnetic separation product reduction and carbonization modification; The carbonization temperature in the carbonization modification process is 600° C.-800° C.; the carbonization time is 5-15 min; and the gas flow rate of ethylene is 5-20 sccm.
2. The method for preparing a wave absorbing material based on reduction carbonization modification of fly ash magnetic separation products according to claim 1, characterized in that: The carbonization temperature in the carbonization modification process is 600° C., 700° C. or 800° C.; the carbonization time is 5 min, 10 min or 15 min; and the gas flow rate of ethylene is 5 sccm, 10 sccm, 15 sccm or 20 sccm.
3. The method for preparing a wave absorbing material based on reduction carbonization modification of fly ash magnetic separation products according to claim 2, characterized in that: The carbonization temperature in the carbonization modification process is 800° C.; the carbonization time is 5 min; and the gas flow rate of ethylene is 5 sccm.
4. The method for preparing a wave absorbing material based on reduction carbonization modification of fly ash magnetic separation products according to claim 1, characterized in that: The preparation method of the fly ash reduction product is: The fly ash is subjected to magnetic separation and hydrogen reduction in sequence to obtain the fly ash reduction product.
5. The method for preparing a wave absorbing material based on reduction carbonization modification of fly ash magnetic separation products according to claim 4, characterized in that: The magnetic separation adopts dry magnetic separation, and the magnetic separation product is obtained after 31 separation rings. The reduction temperature in the hydrogen reduction process is 800° C. and the reduction time is 1 hour.
6. A microwave absorbing material based on reduction and carbonization modification of fly ash magnetic separation products, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 5.
7. The microwave absorbing material based on reduction carbonization modification of fly ash magnetic separation products according to claim 6, characterized in that: The wave absorbing material based on reduction and carbonization modification of fly ash magnetic separation products is a core-shell structure formed by Fe and Fe3C.
8. The microwave absorbing material based on reduction carbonization modification of fly ash magnetic separation products according to claim 6, characterized in that: The strongest reflection loss value of the wave absorbing material based on the reduction and carbonization modification of fly ash magnetic separation products is -39.19 dB at 11.68 GHz, and the matching thickness is 2.5 mm.
Citation Information
Patent Citations
Composite wave-absorbing material based on fly ash as well as preparation method and application of composite wave-absorbing material
CN116693275A
Fly ash hollow microsphere and carbon nanotube porous wave-absorbing microsphere as well as preparation method and application of fly ash hollow microsphere and carbon nanotube porous wave-absorbing microsphere
CN117625135A
Treatment of fly ash
US20090314185A1
METHOD FOR MANUFACTURING SiO-BASED CARBON NANOFIBER COMPOSITE ON BASIS OF NICKEL-COPPER CATALYST USING ELECTROPHORETIC DEPOSITION, AND METHOD FOR MANUFACTURING SECONDARY BATTERY USING SAME
US20160268587A1